Methods and Ways of Teaching Vocabulary at Higher Educational Institution - Ishanxadjayeva Feruza Abduboriyevna (International Journal on Orange Technologies, 2022)
The main purpose of reading is to the extract and comprehends the information contained in written text. In the process of reading, the reader not only perceives information, but also carries out its semantic processing. The relevance of this article should be overestimated, since today there is a tangible need for teachers-practitioners working at universities to get acquainted with both modern theoretical approaches to teaching reading and practical experience - in different educational contexts, in different foreign languages, for different purposes and learning objectives.